Feasibility of small animal cranial irradiation with the microRT system - Kiehl, Erich L.; Stojadinovic, Strahinja; Malinowski, Kathleen T.; Limbrick, David; Jost, Sarah C.; Garbow, Joel R.; Rubin, Joshua B.; Deasy, Joseph O.; Khullar, Divya; Izaguirre, Enrique W.; Parikh, Parag J.; Low, Daniel A.; et al. (Medical physics (Lancaster), 2008)
Purpose: To develop and validate methods for small-animal CNS radiotherapy using the microRT system. Materials and Methods: A custom head immobilizer was designed and built to integrate with a pre-existing microRT animal couch. The Delrin® couch-immobilizer assembly, compatible with multiple imaging modalities (CT, microCT, microMR, microPET, microSPECT, optical), was first imaged via CT in order to verify the safety and reproducibility of the immobilization method. Once verified, the subject animals were CT-scanned while positioned within the couch-immobilizer assembly for treatment planning purposes. The resultant images were then imported into CERR, an in-house-developed research treatment planning system, and registered to the microRTP treatment planning space using rigid registration. The targeted brain was then contoured and conformal radiotherapy plans were constructed for two separate studies: (1) a whole-brain irradiation comprised of two lateral beams at the 90° and 270° microRT treatment positions and (2) a hemispheric (left-brain) irradiation comprised of a single A-P vertex beam at the 0° microRT treatment position. During treatment, subject animals ( n = 48 ) were positioned to the CERR-generated treatment coordinates using the three-axis microRT motor positioning system and were irradiated using a clinical Ir-192 high-dose-rate remote after-loading system. The radiation treatment course consisted of 5 Gy fractions, 3 days per week. 90% of the subjects received a total dose of 30 Gy and 10% received a dose of 60 Gy . Results: Image analysis verified the safety and reproducibility of the immobilizer. CT scans generated from repeated reloading and repositioning of the same subject animal in the couch-immobilizer assembly were fused to a baseline CT. The resultant analysis revealed a 0.09 mm average, center-of-mass translocation and negligible volumetric error in the contoured, murine brain. The experimental use of the head immobilizer added ± 0.1 mm to microRT spatial uncertainty along each axis. Overall, the total spatial uncertainty for the prescribed treatments was ± 0.3 mm in all three axes, a 0.2 mm functional improvement over the original version of microRT. Subject tolerance was good, with minimal observed side effects and a low procedure-induced mortality rate. Throughput was high, with average treatment times of 7.72 and 3.13 min /animal for the whole-brain and hemispheric plans, respectively (dependent on source strength). Conclusions: The method described exhibits conformality more in line with the size differential between human and animal patients than provided by previous prevalent approaches. Using pretreatment imaging and microRT-specific treatment planning, our method can deliver an accurate, conformal dose distribution to the targeted murine brain (or a subregion of the brain) while minimizing excess dose to the surrounding tissue. Thus, preclinical animal studies assessing the radiotherapeutic response of both normal and malignant CNS tissue to complex dose distributions, which closer resemble human-type radiotherapy, are better enabled. The procedural and mechanistic framework for this method logically provides for future adaptation into other murine target organs or regions.